Pengaruh Kualitas Produk, Electronic Word of Mouth (E-WOM) dan Fear of Missing Out (FOMO) Terhadap Minat Beli Iphone Seri 13 Ke Atas pada Generasi Z di Kabupaten Jombang - Sholekah, Lailatus; Nurhayati, Wina; Ammaridho, Evan Andarianto (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to determine the effect of product quality, electronic word of mouth (E-WOM), and fear of missing out (FOMO) on purchasing interest of iPhone series 13 and above among generation Z in Jombang Regency. This study uses a quantitative approach by distributing questionnaires to generation Z in Jombang Regency which are then analyzed using multiple linear regression, t-test and f-test. Sampling uses a non-probability sampling technique with a purposive sampling method to obtain 65 respondents. The results of the t-test in this study indicate that product quality does not significantly influence purchasing interest while electronic word of mouth (E-WOM) and fear of missing out (FOMO) significantly influence purchasing interest of generation Z in Jombang Regency. Simultaneously, the results of the study show that product quality, electronic word of mouth (E-WOM) and fear of missing out (FOMO) simultaneously have a significant effect on purchasing interest. The findings of this study indicate that positive information and reviews on social media and the urge to follow trends have a greater role in increasing purchasing interest than perceptions of product quality.